Valence, Size, and Shape Control of Gold Nanoparticles Synthesized by Electron‐Assisted Reduction. Issue 22 (20th October 2020) - Shi, Mengge; Wang, Zhao
Abstract: An electron‐assisted strategy was developed to prepare gold nanoparticles (AuNPs) at room temperature. Glow discharge plasma as electron source was successfully used to control the valence state, size, and shape of AuNPs. Stable Au(I) was obtained in 3 min by plasma, and Au(I) was reduced to zero valence with the increase in treatment time. An increase in the amount of Au did not induce an increase in particle size. A narrow size distribution was also achieved. The narrowest size distribution was observed at 9 min at 600 V. AuNPs grew slowly under glow discharge plasma, which slightly changed the mean size of AuNPs. Moreover, the average size of AuNPs was smaller under alkaline conditions. The initial pH of the solution can affect the nucleation and growth of AuNPs and further affect their particle size. Spherical AuNPs, hexagonal AuNPs, rectangular AuNPs, flower‐shaped AuNPs, and Au nanorods were easily obtained within 30 min by adding different additives. The hexagonal AuNPs exhibited the largest current response toward caffeine and showed a good linear range (0.1–1000 μM) with a low detection limit (0.064 μM), because their high‐energy planes can increase the electron transfer rate and improve electrocatalytic activity. Abstract : An efficient approach for the control of the valence state, size and shape of AuNPs by glow discharge plasma is presented. Stable Au(I) aqueous solution, spherical AuNPs, hexagonal AuNPs, rectangular AuNPs, flower‐shaped AuNPs, and Au nanorods were successfully prepared at room temperature within 30 min. Besides, hexagonal AuNP‐modified GCE can be used as a high‐efficiency electrochemical sensor for the sensitive detection of caffeine.